Botulinum toxin in management of back pain - Łuczak, Blanka; Nowińska, Bianka; Słychan, Katarzyna; Hądzlik, Izabela; Piotrowski, Jan; Biały-Karbowniczek, Julia; Bulska, Klaudia; Brzozowska, Patrycja; Piela, Andrzej; Sławek, Konrad (Quality in Sport, 2024)
Introduction The botulinum toxin is a widely used therapeutic agent. It is used for aesthetic reasons in treatment of glabellar wrinkles. Therapeutic indications include cervical dystonia, hyperhidrosis or migrenes. Also, it can be used in pain management, especially back pain. Back pain is one of the most common pain syndromes decreasing quality of life. Treatment involves various methods such as conservative and surgical approach. One of the methods is botulinum toxin. Objectives This article aims to evaluate usage, mechanism and treatment effects of back pain using botulinum toxin. Methods A Literature review of articles published in Pubmed between 2000 and 2024 using following words “botulinum toxin”, “botulinum”, “back pain” and “treatment”. Results Botulinum toxin injections are one of the pain management methods used especially in low back pain and myofascial pain syndrome. Treatment relies on its myorelaxant properties and inhibition of neuromodulator secretion such as substance P or acetylocholine. Pain relief effects are noted after three weeks and can last up to six months. In the initial stages a significant amount of patients report relief of pain. Conclusion Botulinum toxin is one of the treatment methods for lower back pain. It is a safe, minimally invasive and effective treatment. Patients can feel the relief even in three weeks and the effects might persist even up to six months.